Engaging Mothers to Implement Nonpharmacological Care for Infants With Neonatal Abstinence Syndrome: Perceptions of Perinatal and Pediatric Nurses. (December 2020) - Shuman, Clayton J.; Weber, Ashley; VanAntwerp, Katherine; Wilson, Roxanne
Abstract : Background: Little is known about nurse perceptions regarding engagement of mothers in implementation of nonpharmacological care for opioid-exposed infants. Purpose: This study was designed to describe perinatal and pediatric nurse perceptions of (1) engaging mothers in the care of opioid-exposed infants and (2) facilitators and barriers to maternal engagement. Methods: This study used a qualitative descriptive design to interview perinatal and pediatric nurses in one Midwest United States hospital. Interviews were conducted via telephone using a semistructured interview guide and audio recorded. Audio files were transcribed verbatim and thematically analyzed using the constant comparative method. Results: Twenty-one nurses participated in the study, representing a family birth center, neonatal intensive care unit, and pediatric unit. Five major themes resulted from analysis: (1) vulnerability and bias; (2) mother–infant care: tasks versus model of care; (3) maternal factors affecting engagement and implementation; (4) nurse factors affecting engagement and implementation; and (5) recommendations and examples of nursing approaches to barriers. Minor themes supported each of the major themes. Implications for Practice: Nurses must engage mothers with substance use histories with empathy and nonjudgment, identify and promote maternal agency to care for their infants, and engage and activate mothers to deliver nonpharmacological care during the hospital stay and following discharge. Implications for Research: Findings suggest interventions are needed to improve (1) nursing education regarding maternal substance use and recovery, (2) empathy for substance-using mothers and mothers in treatment, and (3) identification and support of maternal agency to provide nonpharmacological care to withdrawing infants.